A rare case of vision loss caused by leptomeningeal metastasis of lung adenocarcinoma: a case report and literature review - Li, Zhihua; Chu, Jian; Shen, Wennan; Chen, Junnan; Dong, Yuemei; Zhang, Manze; Zhao, Nan; Zhao, Wei; Zha, Haoran; Wang, Ning; Han, Yalin; Li, Zhaoxia (Frontiers in Oncology, 2025)
Leptomeningeal metastasis (LM) is a fatal complication with increasing incidence in patients with non-small cell lung cancer. Herein, we present the case of a patient who presented with complete vision loss due to LM and achieved a survival benefit from treatment with trametinib. The treatment was prescribed based on the detection of a BRAF non-V600E mutation in the cerebrospinal fluid (CSF). We reviewed the literature and evaluated survival benefits in patients with LM harboring BRAF non-V600E mutations treated with CSF chemotherapy and mitogen-activated extracellular signal-regulated kinase inhibitors.